Securing the Quality and Timely Execution of Transportation Services by Using Outsourcing - Eryk WINIARSKI; Igor BETKIER (Communications of International Proceedings, 2021)
Providers of logistics services should take into account the current needs of customers and changes in them, and should also constantly monitor the services and, if necessary, modify them. A service that delivers high value today may not be sufficient for a customer even in the nearest future. The article proposes a cognitive approach based on experience and general cost assessment. Based on this approach, it was found that optimal decisions were possible only when they were based on long-term cost calculation, a close cooperation of the entities involved, as well as other factors important for the process.
Keywords: Outsourcing; Transport; Logistics; Transport Costs.